Learning geometry in pro-gymnasium: achievements and challenges - Sičiūnienė, Viktorija; Dargytė, Janina (Lietuvos matematikos rinkinys, 2012)
In Lithuania project “Standardized assessment of student achievement and self-assessment tool for schools of general education development” (Phase I) has been carried out for three years. It is the first time testing specialists’, specialists’ in didactics and teacher’s experience have been merged and statistical and expert information have been systematised and generalized. Standardized grade 8 math programme was created, in which for the first time three students’ achievement levels descriptions and illustrated tasks’ examples are presented. Creation of the programme and programme’s presentation to mathematics community gave rise to many discussions about the different students’ achievement levels abilities and reasons for it. Extra-large ability differences emerged in the field of geometry, which encouraged the authors to go deep into the problems of this area. Authors took advantage of the project database and completed geometry tasks and their solutions deep analysis. This article presents the summarized results of the study.
Keywords: student grade 8 achievement in math; geometry-learning; item response theory; productive capacity; achievement levels; reproductive capacity; standardized program